Legal Analysis of Online Buying and Selling Transactions in the Perspective of Sharia Economic Law - Hemansyah, Yus; Hariadi, Fadli; Hasanudin; Badruzaman, Dudi; Muharomah, Nurul Adilatul (Jurnal Ekonomi Syariah Pelita Bangsa, 2023)
Online buying and selling contracts in the perspective of Sharia Economic Law must meet sharia principles so that the transaction is legal and in accordance with Islamic teachings. This study aims to analyze the law of online buying and selling transactions from the perspective of Sharia Economic Law. The research method used is qualitative descriptive with qualitative analysis data analysis. The results of the study show that goods and services that are traded must be halal, in accordance with Islamic teachings. Products that are haram or have haram elements are prohibited in sharia transactions. All information regarding goods, prices, and transaction terms must be conveyed clearly and honestly to avoid gharar (ambiguity) and fraud. The transaction process must include clear offers and receipts, sharia-compliant payments, and fair and transparent delivery and receipt of goods. Sustainability in sharia e-commerce is also an important aspect that needs to be considered, including in products, packaging, and shipping. Despite the challenges in its implementation, long-term benefits such as consumer trust, general welfare, and regulatory support make the application of Sharia Economic Law in e-commerce an important and beneficial strategy.